Network for the Improvement of Addiction Treatment (NIATx), 2003-2007 - McCarty, Dennis ([Verlag nicht ermittelbar], 2012)
The Network for the Improvement of Addiction Treatment (NIATx) is a program funded by the Robert Wood Johnson Foundation and the Center for Substance Abuse Treatment to help substance abuse treatment facilities improve the effectiveness and efficiency of care offered to clients. A total of 38 facilities from across the country were awarded funding to implement the NIATx program between the years of 2003 to 2007. Data were extracted from administrative records from 82,274 clients. The data file covers the dates of contact and treatment with the facility, the number of follow-up units of care received, the primary substance of abuse, and basic demographic information.